Resting Physiologic Dead Space as Predictor of Postoperative Pulmonary Complications After Robotic-Assisted Lung Resection: A Pilot Study - Godbole, Rohit; Church, Sanford B.; Abolhoda, Amir; Porszasz, Janos; Sassoon, Catherine S. H. (Frontiers in Physiology, 2022)
Lung resection surgery carries significant risks of postoperative pulmonary complications (PPC). Cardiopulmonary exercise testing (CPET) is performed to predict risk of PPC in patients with severely reduced predicted postoperative forced expiratory volume in one second (FEV1) and diffusion of carbon monoxide (DLCO). Recently, resting end-tidal partial pressure of carbon dioxide (PETCO2) has been shown as a good predictor for increased risk of PPC. However, breath-breath breathing pattern significantly affects PETCO2. Resting physiologic dead space (VD), and physiologic dead space to tidal volume ratio (VD/VT), may be a better predictor of PPC than PETCO2. The objective of this study was to prospectively determine the utility of resting measurements of VD and VD/VT in predicting PPC in patients who underwent robotic-assisted lung resection for suspected or biopsy-proven lung malignancy. Thirty-five consecutive patients were included in the study. Patients underwent preoperative pulmonary function testing, symptom-limited CPET, and a 6-minute walk test. In the first 2 minutes prior to the exercise portion of the CPET, we obtained resting VT, minute ventilation (V ̇E), VD (less instrument dead space), VD/VT, PETCO2, and arterial blood gases. PPC within 90 days were recorded. Fourteen (40%) patients had one or more PPC. Patients with PPC had significantly elevated resting VD compared to those without (0.318 ± 0.028 L vs. 0.230 ± 0.017 L (± SE), P < 0.01), and a trend toward increased VD/VT (0.35 ± 0.02 vs. 0.31 ± 0.02, P = 0.05). Area under the receiver operating characteristic (ROC) for VD was 0.81 (P <0.01), VD/VT was 0.68 (P = 0.08), and PETCO2 was 0.52 (P = NS). Peak V ̇O2, V ̇E/V ̇CO2 slope, pulmonary function tests, 6-minute walk distance and arterial blood gases were similar between the two groups. Intensive care unit and total hospital length of stay was significantly longer in those with PPC. In conclusion, preoperative resting VD was significantly elevated in patients with PPC. The observed increase in resting VD may be a potentially useful predictor of PPC in patients undergoing robotic-assisted lung resection surgery for suspected or biopsy-proven lung malignancy. A large prospective study is needed for confirmation.